Factors associated with father-to-infant attachment at 6 months postpartum: a community-based study in Victoria, Australia. (14th March 2016) - Wynter, Karen; Rowe, Heather; Tran, Thach; Fisher, Jane
Abstract: Objective: To identify factors associated with father-to-infant attachment at 6 months postpartum. Background: Poor father-to-infant attachment can lead to developmental problems in infants. Some studies suggest that poor paternal mental health may be negatively associated with father-to-infant attachment, but there is currently little evidence about other potential risk factors for poor father-to-infant attachment, such as aspects of the intimate partner relationship and infant characteristics. Methods: A community sample of couples with a first infant was recruited from diverse Local Government Areas. Men completed two telephone interviews, at 4 weeks and 6 months postpartum. Father-to-infant attachment was assessed using the Parental Attachment Questionnaire (PAQ). Other standardised instruments included the Edinburgh Postnatal Depression Scale (EPDS) to assess symptoms of depression and anxiety and the Intimate Bonds Measure (IBM) to assess quality of the intimate partner relationship. The outcome measure was Parental Attachment Questionnaire (PAQ) total score. Structural equation modelling was used to identify factors associated with lower PAQ scores. Results: Total PAQ scores were provided by 270 men. Poorer quality father-to-infant attachment was significantly associated with personality traits like oversensitivity ( p = 0.03), more symptoms of depression and anxiety ( p = 0.02), poorer quality partner relationship ( p = 0.01) and more frequent partner criticism of infant care ( p = 0.01). Conclusion: Fathers should be included in routine postnatal care. Critical behaviour by the partner is a potentially modifiable risk factor for poor father-to-infant attachment. Perinatal primary care health services programmes should focus on building parents' skills to provide sensitive, affirming care for each other and for the infant.